CATALOGUE OF MAIN CHARACTERISTICS OF INDIVIDUAL PULSATIONAL CYCLES OF 35 MIRA-TYPE STARS - Marsakova, V. I.; Andronov, I. L. (Одеські астрономічні публікації, 2017)
The characteristics of individual cycles of 35 Mira-type stars are tabulated: the moments and brightness of the extrema, the inverse slopes dt/dm of the light curves and corresponding error estimates. The observations for the analysis are taken from the AFOEV and VSOLJ databases for the stars: R And, W And, R Aql, R Aur, X Aur, R Boo, T Cam, U Cmi, R Cas, S Cas, T Cas, V Cas, W Cas, S Cep, T Cep, V Cnc, V Crb, χ Cyg, RT Cyg, W Dra, T Gem, U Her, R Hya, R Leo, R LMi, R Lep, R Lyn, W Lyr, X Oph, W Peg, Y Per, R UMa, S UMa, S UMi, T UMi.